Ploughing the Field: Controversy and Censorship in US and UK YA Literature - Emily Corbett; Leah Phillips (International Journal of Young Adult Literature, 2023)
The United States and the United Kingdom have faced a record number of book challenges in recent years. In the US, the American Library Association documented 1,269 demands to censor library books and materials in 2022, nearly double the number of challenges reported in 2021 (ALA n.p.). In the UK, a third of librarians have been asked to censor or remove books from their libraries (CILIP, qtd. in Shaffi n.p.). In both countries, YA texts are among the most banned and challenged books. The assaults on young people’s freedom to read represented by this form of censorship particularly target marginalised identities and experiences: “the majority of banned titles are authored by or about members of the LGBTQ and Black communities” (Diaz n.p.). The ideologies underpinning many book challenges can also be seen in the divisive attacks against transgender people and their right to exist, vitriolic responses to critical race theory, and the elimination of reproductive rights, to name but a few. In short, the personal has become political, as “book challenges represent the movement of a private act (determining what one’s own children should read) into the public sphere” and the attempt to transform personal convictions into “community values and beliefs” (Knox 132). In this iteration of “Ploughing the Field”, we brought together YA experts (see Table 1) who have lived and/or worked in the US and the UK to better understand: some of the recent trends in YA and why they have garnered such strong reactions in the Western milieu; the role that YA can play in the lives of young people; and our responsibilities as teachers and scholars of YA to young readers and each other